Pengembangan Aplikasi E-Commerce Potensi Unggulan Desa untuk Masyarakat Pataro Berbasis Android - Jumadi Mabe Parenreng; Mustari S. Lamada; Jusniar Jusniar (Progressive Information, Security, Computer, and Embedded System, 2023)
This research is a software development that aims to determine the results of testing, effectiveness, development of the E-Commerce application. maintenance, portability. The development model used is the waterfall with the stages of needs analysis, concept design, system coding, system testing, and program implementation, and uses Research and Development (R&D) research methods. Data collected using interview techniques, observation, questionnaires, documentation. The application was validated by two system experts and evaluated by 30 respondents. The data analysis technique used is quantitative descriptive analysis in the form of proportions. Research results obtained based on ISO 25010 testing: (1) suitability of the functionality of the test specifications is worth 1 and has fulfilled the Testing aspect; (2) testing the performance efficiency aspect using Android Studio software, Visual Studio Code with the acquisition of raster max 231.4 ms/frame and avg 26.7 ms/frame and UI max 85.1 ms/frame and avg 4.5 ms/ frame; (3) testing the compatibility aspects of several applications that are run simultaneously to obtain results that can run well; (4) testing the usability aspect to 30 respondents with a score of 90.17%, very good category; (5) testing the reliability aspect with the test results of 200 tests in the dropped statement, namely keys, pointers, trackballs, flips, and rotations worth 0; (6) testing the security aspects with a score (52/100); (7) aspects of maintability testing get notification results if there is an error; (8) testing aspects of portability on several types of smartphones with different Android versions can run well without any problems.